Biomekhanizmy kak osnova sportivnoi tekhniki bor'by - Karashchuk, A. F. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to consider the biomechanisms as the basis of technique in wrestling. The author had analyzed the generally accepted notions of technique. He had discovered the contradictions of various types in the characteristics of «wrestling techniques» notions given by some authors. The results of the sporting-technical structure`s research having been based on the anatomical principles are represented. The author considers the construction of biomechanisms as the system-structure units of wrestling and shows their pequliarities and types .